Pus organisms - Towne, Norman Lee (My University, 1904)
Introduction: Bacteriology as a science,though comparatively in its infancy occupies a foremost position,and the world is fast recognizing it as an important and powerful factor in health and disease. Therefore a fundamental knowledge of bacterial growth and action is of utmost importance. to everyone - however it is not the propart of this thesis to treat such a large subject,but rather to bring out some of the important facts associated with pus producing organisms. Associated with nearly all forms of infectious diseases is a well recognized class of organisms,known as pus producers. To the casual observer the mere mention of pus-organisms brings to mind a certain offensive, ill smelling substance called pus, with no thought of its mode of formation or effect or in medicine or disease. Pus,is a white,yellowish-white, or creamy looking opaque liquid of varying consistancy,produced by the liquefactive necrosis of inter-cellular substances on tissues-the nucleated cells themselves floating in the clear liquid and undergoing fatty degeneration. Most of the pus producers are of the cocci form - the most important ones being Staphlococcus pyogenes aureus and Streptococcus pyogenes,however some bacilli can produce pus.
Citation: Towne, Norman Lee. Pus organisms. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bacteriology; Pus; Bacteria; Health; Theses